Knockdown and overexpression of basolateral amygdala SIRT1 via AAV bidirectionally alter morphine-induced conditioned place preference extinction in mice - Hao, Guo; Mingchen, Yao; Yalin, Zheng; Yaqi, Qu; Tingwu, Yang; Xinru, Xing; Kaixuan, Li; Yani, Dong; Dongsen, Liu (Frontiers in Cellular Neuroscience, 2025)
IntroductionThis study investigates the role of SIRT1 in basolateral amygdala (BLA) glutamatergic neurons in morphine-induced conditioned place preference (CPP).MethodsVia SIRT1 knockdown/overexpression in bilateral BLA of morphine-induced CPP mice. Outcomes measured by behavioral tests, WB, and transmission electron microscopy.ResultsWe found that SIRT1 knockdown prolonged CPP extinction and enhanced reinstatement, whereas overexpression accelerated extinction and attenuated relapse. Behavioral tests revealed that SIRT1 knockdown rescued morphine-induced memory impairment and anxiety-like behaviors, while overexpression exacerbated these effects. Ultrastructural and molecular analyses demonstrated SIRT1 modulation of synaptic plasticity-related proteins (BDNF, PSD95) and synaptic ultrastructure in BLA.DiscussionOur findings reveal that SIRT1 bidirectionally regulates opioid-associated memory persistence through synaptic remodeling, highlighting its potential as an epigenetic target for addiction treatment. While SIRT1 is implicated in neuroplasticity, its specific role in modulating opioid-associated memory circuits within the BLA remains undefined, representing a critical gap in understanding addiction neuropathology.